واقع و آفاق تطوير الطاقات المتجددة في البلدان المغاربية (الجزائر،تونس و المغرب) - الشيخ, نورالدين; بوعراب, رابح (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى الوقوف على واقع و امكانيات الطاقة المتجددة في كل من الجزائر، المغرب و تونس و آفاق تطوّرها في المستقبل، من خلال التطرق إلى الوضعية الحالية لحصة الطاقات المتجددة في ميزان الطاقة و كذا واقع الإنتاج. بالإضافة إلى عرض أهم العوائق التي تقف حاجزا أمام تطورها وانتشارها. وتظهر النتائج أن الطاقة المتجددة لا تزال تمثل دورا هامشيا في مزيج الطاقة في كل من الجزائر و تونس، بخلاف المغرب الذي يمر بمرحلة انتقالية في مجال الطاقة لا سيما الطاقة الشمسية و طاقة الرياح، لكن لا يزال يتعيّن اتخاذ سلسلة من الإجراءات الحاسمة التي تسهل تحقيق هدف حصة الطاقة المتجددة لعام 2030. This study aims to identify the reality and potential of renewable energy in Algeria, Morocco and Tunisia and the prospects for its development in the future, by addressing the current situation of the share of renewable energies in the energy balance as well as the reality of production. In addition to presenting the most important obstacles that stand in the way of its development and spread. The results show that renewable energy still plays a marginal role in the energy mix in Algeria and Tunisia, unlike Morocco, which is going through an energy transition, especially solar and wind energy, but a series of decisive measures that facilitate the achievement of the goal are still to be taken. The share of renewable energy for 2030 .
The reality and prospects for developing renewable energies in the Maghreb countries (Algeria, Morocco, Tunisia(
مقال
Keywords: الطاقات المتجددة، الطاقة الشمسية، طاقة الرياح، البلدان المغاربية; renewable energies ; solar energy ; wind energy ; Maghreb countries